2007
DOI: 10.1016/j.bcp.2007.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacological analysis of Rho-kinase inhibitors and identification of molecular components of Ca2+ sensitization in the rat lower urinary tract

Abstract: We aimed to compare the expression and function of molecular components of the RhoA/Rho-kinase signaling pathway in the contractile responses of detrusor, trigonal and urethral smooth muscle, using selective Rho-kinase inhibitors. Contractility studies and molecular approaches were employed to demonstrate the expression patterns and functional activity of the RhoA/Rho-kinase signaling pathway in the lower urinary tract. Frequency-response curves (1-32 Hz) and concentration-response curves (CRC) to carbachol (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…For example, Deplanne et al found that α,β -methylene ATP contracted all regions of rabbit urethra 7 and Teixeira et al noted that α,β -methylene ATP also contracted strips of rat USM. 19 Hashitani and Edwards reported that EFS of intramural nerves in guinea pig USM yielded excitatory junction potentials and slow waves, which were inhibited by α,β -methylene ATP. 9 Bradley et al described a transient inward current in urethral SMCs that was activated by ATP but not mimicked by the P2Y agonist 2-MeSADP.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Deplanne et al found that α,β -methylene ATP contracted all regions of rabbit urethra 7 and Teixeira et al noted that α,β -methylene ATP also contracted strips of rat USM. 19 Hashitani and Edwards reported that EFS of intramural nerves in guinea pig USM yielded excitatory junction potentials and slow waves, which were inhibited by α,β -methylene ATP. 9 Bradley et al described a transient inward current in urethral SMCs that was activated by ATP but not mimicked by the P2Y agonist 2-MeSADP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, components of the RhoA-Rho-kinase signaling pathway are expressed in detrusor, trigonal and urethral smooth muscle and dynamically regulate contraction and tone. Moreover, Rho-kinase inhibitors also markedly reduced the contractions evoked by either KCl or α , β -methylene ATP with H-1152 was approximately 9 -16 times more potent than Y-27632 or HA-1077 [107] .…”
Section: Rho Kinasesmentioning
confidence: 96%
“…A role for RhoA and ROK in urethral tone was indicated by the demonstration that inhibition of RhoA with Clostridium difficile toxin B or of ROK with Y27632 abolished porcine urethral tone without affecting [Ca 2ϩ ] i (28). ROK inhibition also inhibited the contractile response of rat urethral smooth muscle to phenylephrine, endothelin-1, ␣,␤-methylene ATP, and membrane depolarization but had no significant effect on baseline tension (37).…”
mentioning
confidence: 99%